Transport demand management - Impacts on congestion alleviation and road safety enhancement in urban areas - Kim Jraiw (19807236) (2015)
Most of the world's population and economic growth is occurring in the cities. Essential as the movements of people and goods are to the economic and social aspects of urban life, they present people and their surrounding with the ever-increasing problems. As a consequence, world's cities face traffic congestion associated with imbalance of the available road space and operation vehicles, slow traffic flow, poor access to main activity centers, high transport cost, waste of time, psychological effects, decline productivity and increase discomfort. Vehicle emissions have their economic and health effects. Road accidents and their fatalities and injuries, pedestrian movements, socioeconomic impacts, inefficient road infrastructure, and unsafe design are also critical issues. To overcome urban transport problems, the UN Habitat has stressed that the conventional solutions of transport planning have proven their inefficiency during the past decades. The pattern and cost of land use, urban structure, population distribution, tight budget, stand-alone projects, lack of expertise, and other factors restrict the impose of successful road facility. Besides, maximizing road network capacity is not the only solution to tackle transport problems, due to the facts of high demand for urban road space and less supply, transport problems are accelerating at higher rate than population and economic growth, and building new road infrastructure requires long period due to complex project cycles. Introduction of the traditional traffic management measures to control vehicle operations is also proved partial solution. Transfer from private vehicles to public transport use is not fully acceptable solution by majority of the community in some countries beside lack of current public transport services. Another serious obstacle is institutional, due to involvement of several organizations in the transport sector, lack of interagency coordination, insufficient enforcement, unavailability of common policy and performance indicators, and insufficient information. Community concern about transport efficiency and the negative drawbacks has increased. Politician and government agencies face increasing pressure to protect the quality of urban environment, create livable cities, maintain the right access and run efficient and integrated transport system. At present, Transport Demand Management (TDM) is emerging as a fashionable concept among planners and decision-makers for sustainable urban development and minimizing transport drawbacks, since traditional transport techniques have reached their effective limits in most cities. The paper addressee merits of the TDM which aim to modify trip makers behavior and habits, reduce use of private vehicles (drive-alone transport), influence mode choice, minimize travel time, alleviate congestion and enhance road safety. Assessment is presented into the practical techniques of the TDM such as congestion charging, public transport priorities, sustainable road network development, ridesharing schemes, service centers, transport-land use planning, communications, restricting use of road space and vehicles, private sector programs, school programs, working hour schemes, and traffic monitoring centers. The paper also explores development conditions, programs and performance of the TDM systems in different parts of the world such as London, Singapore, Stockholm, Dubai and Victoria (Australia) which alleviated congestion, enhanced road safety, and promoted equity in transport accessibility for passengers, pedestrians, freight, community and economic viability. The paper stresses that TDM is the only sustainable approach to accommodate the ever-increasing demand for travel and tackle transport problems, as part of a comprehensive and balanced policy for today and future cities. Other Information Published in: Journal of Local and Global Health Science, title discontinued as of (2017) License: https://creativecommons.org/licenses/by/4.0/ See article on publisher's website: https://dx.doi.org/10.5339/jlghs.2015.itma.83